Influence of Stressful Life Events and Cognitive Styles on Academic Achievements of Undergraduates of School of Continuing Education, Bayero University Kano - Muktar, M. A.; Iliyasu, S.; Zandam, B. U.; Abubakar, B.; Tukur, A. M.; Karaye, K. M. (Journal of Research in Adult and Continuing Education, 2026)
Academic achievement among university students is influenced by numerous psychological, cognitive, and demographic factors. This study investigated the influence of stressful life events and cognitive styles on academic achievement among undergraduates of the School of Continuing Education, Bayero University Kano, Nigeria. The study adopted an ex-post facto research design. The population comprised 975 Level 400 undergraduates, while a sample of 278 students was selected using a multistage sampling procedure. Data were collected using the Group Embedded Figures Test (GEFT) for cognitive styles, the Kanjiga Stressful Life Events Inventory (KSLEI) for stressful life events, and students' cumulative grade point averages (CGPA) as indicators of academic achievement. Frequency counts and independent samples t-test were employed for data analysis at the 0.05 level of significance. The findings show that most students (60.4%) experienced high stressful life events, compared to 39.6% who reported low stress, no significant difference in academic achievement between field dependent and field independent students, no significant difference in academic achievement between students with high and low stressful life events, even though the high-stress group recorded a slightly higher mean CGPA.  The study recommends the provision of effective counselling services, stress-management programmes, and learner-centred instructional approaches that accommodate diverse cognitive styles among adult learners.
Keywords: Academic achievement; cognitive styles; continuing education; stressful life events; undergraduate students